قضية البيئة في الخطاب الإسلامي المعاصر (دراسة تحليلية في فكرة عبد المجيد النجار): The Issue of the Environment in Contemporary Islamic Discourse (an Analytical Study of the Idea of ​​Abdel Majeed Al-Najjar) - Masruri, Muhammad; Fattah, Mohammad; Amalih, Ihwan (Jurnal Adabiyah, 2024)
This article seeks to examine an important issue widely discussed among Muslim thinkers, namely environmental issues. The main cause of the emergence of the environmental crisis cannot be separated from the paradigm used by modern civilization towards the environment and this crisis cannot be overcome except by changing the paradigm used in viewing the environment. So this study will portray the phenomenon of environmental crisis and solutions in overcoming the problem from the perspective of contemporary Islamic discourse by analyzing the ideas offered by Abdul Majid Al-Najjar. The method used by the author in this study is a qualitative research method, by elaborating reference sources that are relevant to the topic of study. The theory used in this research is the theory of ecological philosophy of Arne Naess. The results of this study are: First, the concept of environment in Islamic discourse according to Abd al-Majid al-Najjar includes two important lines, namely: The spiritual reality of the environment, which views that the environment is a manifestation of divinity where God's attributes are revealed through environmental reality. The material reality of the environment is the substance of reality that exists in the real world. These two environmental realities cannot be separated from each other in viewing the environment. Second, in caring for the environment, Abdul Majid Al-Najjar uses the term “irtifaq” which is a combination of meanings between the utilization of natural resources and environmental preservation simultaneously. The ethics of natural resource utilization must be carried out proportionally according to needs, while the ethics of environmental preservation include maintaining the environment from damage, pollution, and pollution. الملخص تبحث هذه المقالة عن دراسة قضية مهمة وخطيرة التي تتم مناقشاتها حاليا في نطاق واسع عند العلماء والمفكرين المسلمين وهي قضية البيئة في الخطاب الإسلامي المعاصر. إن السبب الأصلي في ظهور الأزمة البيئية هو التصور الفكر الثقافي الذي حمله إنسان الحضارة الحديثة عن البيئة، وأن معالجة هذه الأزمة معالجة حقيقية لا تتحقق إلا بتغيير فكري ثقافي عميق لهذا التصور الثقافي. ولذلك تركز هذه الدراسة على الجهود المبذولة لتصوير ظواهر الأزمات البيئية المنتشرة في العالم وطريق معالجتها من منظور التصور الثقافي الإسلامي بتحليل عن فكرة عبد المجيد النجار. وأما النظرية المستخدمة في هذا البحث فهي نظرية الفلسفة الإيكولوجية لأرني ناييس. وأما نتائج هذا البحث فهي: الأولي، إن مفهوم البيئة في التصور الخطاب الإسلامي عند عبد المجيد النجار يشتمل على خطان، وهي: الحقيقة الروحية للبيئة التي تعتبر بأن البيئة من التجلى الإلهى وتتجلى فيه صفات الله. والحقيقة المادية للبيئة التي تعتبر أنها مادة واقعية حقيقية ليست مجرد وجود ذهني أو عقلي أو خيالي، إن هذان خطان لا ينفك أحدهما عن الأخر في تصور الحقيقة البيئية. الثانية، استخدم عبد المجيد النجار مصطلح "إرتفاق" عبارة على أن لفظ الإرتفاق يجمع في مادته معنى النفع ومعنى اللطف، وطريقة إرتفاق البيئة يشتمل على الإستنفاع البيئي بشكل متوازن مع الاحتياجات دون اسراف والرفق بالبيئة الذي يشتمل على الرفق الصياني والرفق الإستهلاكي من الفساد، والتلف، والتلوث. Abstrak Artikel ini berupaya untuk mengkaji isu penting yang marak diperbincangkan di kalangan pemikir muslim yaitu isu lingkungan. Penyebab utama munculnya krisis lingkungan hidup tidak bisa dilepaskan dari paradigma yang digunakan oleh masyarakat peradaban modern terhadap lingkungan hidup dan krisis ini tidak bisa diatasi kecuali dengan perubahan paradigma yang digunakan dalam melihat lingkungan. Maka kajian ini akan memotret fenomena krisis lingkungan serta solusi dalam mengatasi problem tersebut ditinjauan dari perspektif wacana keislaman kontemporer dengan menganalisis gagasan yang ditawarkan oleh Abdul Majid Al-Najjar. Adapun metode yang digunakan penulis dalam kajian ini adalah metode penelitian kualitatif, dengan mengelaborasi sumber referensi yang relevan dengan topik kajian. Sedangkan teori yang digunakan dalam penelitian ini adalah teori filsafat ekologi Arne Naess. Adapun hasil dari penelitian ini adalah: Pertama, konsep lingkungan dalam wacana keislaman menurut Abd al-Majid al-Najjar mencakup dua garis penting, yaitu: realitas spiritual dari lingkungan, yang memandang bahwa lingkungan adalah dari manifestasi ketuhanan dimana sifat-sifat Tuhan ditampakkan melalui realitas lingkungan. Adapun realitas material dari lingkungan merupakan substansi realitas yang ada dalam dunia nyata. Kedua realitas lingkungan ini tidak dapat dipisahkan satu sama lain dalam melihat lingkungan. Kedua, Dalam merawat lingkungan, Abdul Majid Al-Najjar menggunakan istilah “irtifaq” merupakan gabungan makna antara pemanfaatan sumber daya alam dan pelestarian lingkungan secara bersamaan. Etika pemanfaatan sumber daya alam harus dilakukan secara proporsional sesuai dengan kebutuhan, sedangkan etika pelestarian lingkungan meliputi pemeliharaan lingkungan dari kerusakan, pencemaran dan polusi.